A Study on the Impact of Experiencing ‘Cultural Heritage’ in Digital Environment on Urban Memory and Future Scenarios - Akgün, Seda Nehir; Akgün, Atacan (ICONARCH International Congress of Architecture and Planning, 2017)
This study aims to investigate the impact of using digital technologies on representation of multi-cultural heritage sites and its possible consequences on ‘memory’ of the place by literature survey and theoretical proposals. Multi-cultural is the keyword, because being settled at a strategic point from many aspects such as liveability, vitality or security cause the further civilizations have settled on the footprints of previous civilizations. Consequently, settlements turned into multi-layered areas mostly and a conservation problem occurs due to representation of such a cultural diversity or historic and architectural continuity. Urban settlements have important phases, which were significant and represents the characteristic of a specific period. Accordingly, representation of significant periods of the past of urban settlements is vital and also important to create and sustain of the urban memory. Conventional conservation and representation technics are not enough to provide a sustainable conservation process, because if the audience would not appropriate the cultural heritage, they do not endeavour for preserving it. However, it is mostly not possible to experience all the previous layers at multi-cultural heritage sites. In single building scale, it is harder in comparison with in urban archaeology scale due to following the urban topography at least for experts is possible. Still, to foster public awareness and attraction, alternative methods are being tried to represent the cultural heritage, because a sustainable conservation needs participation of the audience. CAVE (Computer Aided Virtual Environment) and BIM (Building Information Modelling) are the examples of creation of built environment in digital context. CAVE is the one, which creates a digital environment to feel and live in; on the other hand, BIM is the source for documentation. Whereas the documentation is the first and the most important phase of conservation, representation of documented heritage is the final phase and these processes are integrated. However, they should be discussed considering their impact on spirit of the place. Is it possible to experience the place without losing spirit of the place in a digital environment? Or, does it help the audience feel, understand and keep the memory of the place? For the future scenarios, cultural heritage sites or cities can be produced -without demolishing the existed ones- in digital environment for keeping the significant periods and contribution to urban memory.